2019
DOI: 10.3390/dj7030066
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Eating Behaviors and Symptoms of Oral Frailty Using Questionnaires

Abstract: A questionnaire survey was conducted to investigate eating behavior and the subjective symptoms of oral frailty, and to examine the relationship between them. A total of 744 subjects with ages over 65 years were included. The questionnaire comprised 18 question items indicating eating behavior and seven question items indicating oral frailty. All items were assessed according to 4 grades on a scale of 1 (not applicable) to 4 (applicable). The total score of oral frailty gradually increased with age. Regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…After initial screening of 835 titles and abstracts, 70 articles were selected for full-text review, 26 of which were included in qualitative synthesis of this review (Figure 1). Seventeen of the studies were cross-sectional [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] (Table 1), and nine were longitudinal [41][42][43][44][45][46][47][48][49] (Table 2). Despite being the innovative focus of this review, none of the studies encountered were translational in nature by either engaging a dentist in administering frailty assessment or utilising frailty status for dental treatment planning or gauging prognosis for oral health outcomes.…”
Section: Study Selectionmentioning
confidence: 99%
“…After initial screening of 835 titles and abstracts, 70 articles were selected for full-text review, 26 of which were included in qualitative synthesis of this review (Figure 1). Seventeen of the studies were cross-sectional [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] (Table 1), and nine were longitudinal [41][42][43][44][45][46][47][48][49] (Table 2). Despite being the innovative focus of this review, none of the studies encountered were translational in nature by either engaging a dentist in administering frailty assessment or utilising frailty status for dental treatment planning or gauging prognosis for oral health outcomes.…”
Section: Study Selectionmentioning
confidence: 99%
“…The association between oral function and physical frailty has been clarified in recent works [1][2][3][4]. In light of this association, the concept of oral frailty was conceptualized as an accumulated poor oral status, and its relation to frailty has been studied [5,6]. Oral frailty is defined as a series of phenomena and processes.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from describing oral frailty as decline in oral function or loss of oral function, Dibello et al proposed that the loss of oral function is driven by a set of impairments that worsen oral daily functions—eg, loss of teeth, poor oral hygiene, inadequate dental prostheses, or difficulty in chewing associated with age-related changes in swallowing [ 27 ]. Likewise, Minakuchi et al [ 28 ], Hihara et al [ 9 ], and Doi et al [ 29 ] specifically described the manifestations of oral frailty.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, many researchers proposed similar definitions for oral frailty. They indicated that oral frailty is a mild decline in oral function, deterioration of oral function or loss of oral function [7][8][9][19][20][21][22][23][24][25][26], and proposed that oral frailty is a precursor or accelerator of general frailty [9,19,20,25].…”
Section: Use Of Oral Frailty In Medicinementioning
confidence: 99%
See 1 more Smart Citation